Exercises to prevent lower limb injuries in youth sports: cluster randomised controlled trial - Olsen, Odd-Egil (BMJ Publishing Group Ltd., 2005)
Objective To investigate the effect of a structured warm-up programme designed to reduce the incidence of knee and ankle injuries in young people participating in sports. Design Cluster randomised controlled trial with clubs as the unit of randomisation. Setting 120 team handball clubs from central and eastern Norway (61 clubs in the intervention group, 59 in the control group) followed for one league season (eight months). Participants 1837 players aged 15-17 years; 958 players (808 female and 150 male) in the intervention group; 879 players (778 female and 101 male) in the control group. Intervention A structured warm-up programme to improve running, cutting, and landing technique as well as neuromuscular control, balance, and strength. Main outcome measure The rate of acute injuries to the knee or ankle. Results During the season, 129 acute knee or ankle injuries occurred, 81 injuries in the control group (0.9 (SE 0.09) injuries per 1000 player hours; 0.3 (SE 0.17) in training v 5.3 (SE 0.06) during matches) and 48 injuries in the intervention group (0.5 (SE 0.11) injuries per 1000 player hours; 0.2 (SE 0.18) in training v 2.5 (SE 0.06) during matches). Fewer injured players were in the intervention group than in the control group (46 (4.8%) v (76 (8.6%); relative risk intervention group v control group 0.53, 95% confidence interval 0.35 to 0.81). Conclusion A structured programme of warm-up exercises can prevent knee and ankle injuries in young people playing sports. Preventive training should therefore be introduced as an integral part of youth sports programmes.